LA COVID 19 DANS LA VILLE DE TOUBA : DE LA RÉSISTANCE À LA RÉSILIENCE COMMUNAUTAIRE. - TOURE, Mamadou Ndong (harmattan, Sénégal, 2023)
This article comes from the research project "Transmission of Covid 19 in Senegal: analysis of the socio-spatial dynamics of the factors of propagation in the region of Dakar and the town of Touba", implemented by the LEIDI Laboratory of the Gaston Berger University from 2021 to 2022 (02 years). It analyses the problem of community perception of the COVID-19 pandemic and its evolution in the town of Touba. It takes stock of the factors involved in resistance to and denial of the disease, and of the occupational categories most affected (commerce and transport). The overall aim of the study is to contribute to a better understanding of the community dynamics that prevailed during the Covid 19 pandemic in the city of Touba. Specifically, the aim is to question community players about their perception of the disease, and then the characteristics that explain the spread of the pandemic, particularly in terms of trade and transport. The methodology is based on the overall methodology of the research project mentioned above. The tools of the Active Participatory Research Method were favoured because of their ability to capture socio-economic realities through focus groups, interviews and testimonials, which we combined with a survey of 500 individuals from different socio-professional categories. The main findings are that community-based approaches should be favoured to deal with pandemics and future epidemics. Community transmission is generally linked to the precarious living conditions of a population that is often hard-working and obliged to travel every day in search of daily expenses in places open to the public, notably markets and bus stations.
Keywords: Covid 19; Perception; Transmission communautaire; Résilience; Ville deTouba